Coincidence of Small-scale Spatial Discontinuities in Leaf Morphology and Nuclear Microsatellite Variation of Quercus petraea and Q. robur in a Mixed Forest - Gugerli, F. (Oxford University Press, 2007)
BACKGROUND AND AIMS: The taxon complex comprising Quercus petraea and Q. robur shows distinct morphologies and ecological preferences, but mostly low differentiation in various types of molecular markers at a broad spatial range. Local, spatially explicit analyses may reveal patterns induced by microevolutionary processes operating mainly over short distances. However, no attempts have been made to date to explore the potential of spatial analyses combining morphological and genetic data of these oaks. METHODS: A mixed oak stand was studied to elucidate the small-scale population genetic structure. All adult individuals were classified and putative hybrids were identified using multivariate discrimination analysis of leaf morphological characters. Likewise, all trees were genotyped with five nuclear microsatellites, and a Bayesian assignment method was applied based on maximum likelihood of multilocus genotypes for taxon and putative hybrid classification. KEY RESULTS: Multivariate analyses of leaf morphological data recognized two groups with few individuals as putative hybrids. These groups were significantly differentiated at the five microsatellites, and genetic taxon assignment coincided well with morphological classification. Furthermore, most putative hybrids were assigned to the taxon found in their spatial neighbourhood. When grouping trees into clusters according to their spatial positions, these clusters were clearly dominated by one taxon. Discontinuities in morphological and genetic distance matrices among these clusters showed high congruence. CONCLUSIONS: The spatial–genetic analyses and the available literature led to the assumption that reproductive barriers, assortative mating, limited seed dispersal and microsite-induced selection in favour of the locally adapted taxon at the juvenile stage may reinforce taxon-specific spatial aggregation that fosters species separation. Thus, the results tend to support the hypothesis that Q. petraea and Q. robur are distinct taxa which share a recent common ancestry. Occasional hybrids are rarely found in adults owing to selection during establishment of juveniles.